Facilitating dynamic schedules for healthcare professionals - CLARKE, SIOBHAN (IEEE, 2006)
Healthcare professionals working in highly dynamic hospital environments typically have correspondingly dynamic schedules that are difficult to manage. Emergent tasks and shifting priorities result in existing schedules becoming obsolete. Pervasive computing technology can aid Healthcare professionals in organising daily activities by exploiting knowledge of planned and emerging tasks, of patients and colleagues, and of the general state of the working environment. The Hermes software framework at Trinity College Dublin supports the development of mobile applications for human activity management that exploits such environmental knowledge. Supported applications are based on the concept of a trail. This paper describes the Hermes framework and illustrates how it can be used to implement applications that can automatically reorganise the schedules of healthcare workers based on sensed changes in their environment
Pervasive Health Conference and Workshops, 2006
1st International Conference on Pervasive Computing Technologies for Healthcare
PUBLISHED
Keywords: health informatics; Hermes software framework; context-aware scheduling; pervasive computing; trails; healthcare